Innesti di cellule staminali mesenchimali nelle grandi perdite di sostanza - Toro, G.; Prinzo, L.; Gison, M.; Di Fino, C.; De Cicco, A.; Braile, A.; Lepre, F.; Toro, A.; Schiavone Panni, A. (Lo Scalpello - Journal, 2019)
THE USE OF MESENCHYMAL STEM CELLS IN SEVERE BONE LOSS Severe bone loss is a critical issue in trauma and it requires complex techniques to preserve limb form and function. Regenerative medicine, using stem cells and molecular biology, might be useful to enhance bone healing in severe bone loss. Between 2017 and 2018, 4 patients showed severe bone loss. In all of them, the use of stem cells was added to fixation with a cortical graft. Fracture healing occurred in a range of 3 to 8 months. In our experience, the use of stem cells, in association with bone graft and stable fixation, was able to achieve bone healing even in case of severe bone loss.